2013
DOI: 10.1159/000357405
|View full text |Cite
|
Sign up to set email alerts
|

Rate-Related Kinematic Changes in Younger and Older Adults

Abstract: Aims: This study aimed to investigate the effects of speech rate changes on kinematic characteristics and stability of speech movements in younger and older speakers using electromagnetic midsagittal articulography. Patients and Methods: Eight young adults and 8 older adults engaged in a series of syllable repetition tasks of /pa/, /sa/ and /ta/ obtained at self-paced slow, habitual and fast speech rates, as well as in a series of metronome-guided speech rates, ranging from 2 to 4 syllables per second. The kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Correlations between speakers' mean normalized F1 and F2 were calculated using Pearsons's r. A correction to adjust for multiple statistical tests was not applied, as this creates an unacceptably high probability of making a Type II error in analyses with small group sizes (Nakagawa, 2004). Rather, multiple comparisons are accounted for in the interpretation of the results (conform e.g., Rothman, 1990;van Brenk, Terband, van Lieshout, Lowit, & Maassen, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between speakers' mean normalized F1 and F2 were calculated using Pearsons's r. A correction to adjust for multiple statistical tests was not applied, as this creates an unacceptably high probability of making a Type II error in analyses with small group sizes (Nakagawa, 2004). Rather, multiple comparisons are accounted for in the interpretation of the results (conform e.g., Rothman, 1990;van Brenk, Terband, van Lieshout, Lowit, & Maassen, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although references to speed-accuracy tradeoffs can be frequently found in the speech motor control literature (e.g., Bennett, van Lieshout, & Steele, 2007;Goozee et al, 2005;Guenther, 1995;van Brenk et al, 2013), so far only few studies have directly addressed this assertion. For example, a recent study reported moderate associations between movement time and the estimated difficulty level of an articulator to reach its target (Lammert, Shadle, Narayanan, & Quatieri, 2018) suggesting that talkers adjust their articulatory speed to ensure adequate articulatory precision during speech.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggests a role for cognition in age-related changes to speech (e.g. Bilodeau-Mercure & Tremblay, 2016;Sadagopan & Smith, 2013, Van Brenk et al, 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests a speed-accuracy trade-off to compensate for physiological changes, such as muscular atrophy to the tongue (Goozée et al, 2005). Although, younger and older adults can repeat syllables at a similar rate when prompted (van Brenk et al, 2014), suggesting that physiological changes are minimally disruptive to speech. Importantly, older adults may choose to speak slower to enable online monitoring of speech, broadly proposing a role for cognition.…”
Section: Motor Speech Changes With Agingmentioning
confidence: 99%